Wide Bezel Televisions Decrease Immersive Experiences. (1st September 2020) - Kong, Hwayeon
Abstract : This study explored how telepresence could be affected by stimuli from reality that distracts people while they are watching television. The sample comprised of 36 undergraduate and graduate students from a university in South Korea (age range: 18–38 years, M  = 22.61, and SD = 4.12). A between-subjects experimental design was employed with two types of viewing equipment (a television screen vs. a television screen with side screens that act as stimuli from reality) and two bezel widths (2 cm vs. 10 cm) to examine how each condition influenced the viewers' perceived telepresence. The results revealed that participants' perception of telepresence was not affected by the type of viewing equipment. However, the level of telepresence was affected by the bezel width: the thinner the bezel, the more telepresence felt by the viewers. These findings provide important insights that can guide the future designs of screen bezels for televisions and other devices in order to more effectively create immersive virtual worlds. Future studies are needed to examine the relationship between central vision and telepresence.